About the Calculation of the Compliance Value and its Practical Relevance - Westhausen, Hans-Ulrich (Ekonomika, 2021)
Corporate investment in compliance in general and compliance management systems (CMS) in particular, follow the cardinal management obligation to always obey the law (so-called “management duty to legality”). But does the compliance function as any other corporate investment really add value favoring all shareholders? The socially desired answer should be probably “yes”, but the business reality shows a different picture: the measurement of the compliance value is a “blind spot” in the scientific theory and research as well as in the corporate practice. This paper analyzes reasons for that “blind spot” and explores the systematization of the compliance value drivers setting up a practical model that monetarizes these effects as well as calculating the added value and ROI of compliance. The author concludes that this quantification is particularly relevant to practice, as the compliance function must be able to measure the quantified impact(s) of the compliance function in order to demonstrate its value to management, shareholders, as well as all interested parties, and to justify and strengthen its role increasing the effectiveness of the CMS as part of the company’s “second line of defense”.